Discriminatory Discursive Strategies in Online Comments of a Vice Indonesia YouTube Video - Kinasih, Tika Ageng Ayu; Yannuar, Nurenzia; Subiyanto, Arif (JoLLA: Journal of Language, Literature, and Arts, 2022)
Abstract: Timor Leste is currently promoting LGBTQ rights. In stark contrast to their beliefs, every year, the country celebrates the annual Pride Parade in the capital city of_Dili. This study focuses on a YouTube channel named Vice Indonesia which has visited and reported on the annual Pride Parade celebration in Dili. The focus of this paper is to analyze the discriminatory discursive strategies that are present in the comments section of the video and how people perceive LGBTQ in Timor Leste after watching the video. Discriminatory discursive strategies by Flowerdew et al. (2002) have been reviewed and used in this study to analyze negative comments. The results showed that four discursive strategies, namely: (1) negative other presentation, (2) scare tactics, (3) blaming the victim, and (4) delegitimation were found in the comments section. Positive and supportive comments exist but are hidden behind negative comments. In addition, this study has offered some insights into how Indonesians perceive LGBTQ by watching the LGBTQ Pride Parade that was celebrated in Dili, Timor Leste. Keywords: discriminatory discursive strategies; negative other presentation; scare tactics; blaming the victim; delegitimation Abstrak: Timor Leste saat ini sedang mempromosikan hak-hak LGBTQ. Sangat kontras dengan kepercayaan mereka anut, setiap tahun, negara ini merayakan Pride Parade tahunan di ibu kota Dili. Studi ini berfokus pada saluran Youtube bernama Vice Indonesia yang telah mengunjungi dan memberitakan perayaan tahunan Pride Parade di Dili. Fokus studi ini adalah menganalisis strategi diskursif diskriminatif yang ada di bagian kolom komentar video dan bagaimana orang memandang LGBTQ di Timor Leste setelah menonton video tersebut. Strategi diskursif diskriminatif oleh Flowerdew et al. (2002) telah ditinjau dan digunakan dalam penelitian ini untuk menganalisis komentar negatif. Hasil penelitian menunjukkan bahwa empat strategi diskursif, yaitu: (1) presentasi negatif lainnya, (2) taktik menakut-nakuti, (3) menyalahkan korban, dan (4) delegitimasi ditemukan di bagian komentar. Komentar positif dan mendukung juga ada tetapi tersembunyi di balik komentar negatif. Selain itu, penelitian ini telah menawarkan beberapa wawasan tentang bagaimana orang Indonesia memandang LGBTQ dengan menonton Parade Pride LGBTQ yang dirayakan di Dili, Timor Leste. Kata kunci: strategi diskursif diskriminatif; presentasi negatif lainnya; taktik menakut-nakuti; menyalahkan korban; delegitimasi